Pharmacological evaluation of imidazole‐derived bisphosphonates on receptor activator of nuclear factor‐κB ligand‐induced osteoclast differentiation and function. (6th August 2020) - Lin, Jianguo; Peng, Ying; Liu, Qingzhu; Li, Ke; Lv, Gaochao; Seimbille, Yann; Huang, Gang; Gao, Feng; Qiu, Ling
Abstract: Bisphosphonates (BPs) have been commonly used in the treatment of osteolytic bone lesions, such as osteoporosis and osteogenesis imperfecta. However, serious side‐effects can occur during the therapy. To search for novel potent BPs with lower side‐effects, a series of imidazole‐containing BPs (zoledronic acid [ZOL]; ZOL derivatives by substitution of the hydrogen at the 2‐position on the imidazole ring with a methyl [MIDP], ethyl [EIDP], n ‐propyl [PIDP], or n ‐butyl group [BIDP]) were developed and the effects on receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast differentiation were investigated using the murine macrophage RAW 264.7 cells at the protein, gene, and morphological and functional levels. Influences of these BPs on the cell growth and proliferation of RAW 264.7 were also studied in order to determine cytotoxicity. The results showed that PIDP significantly inhibited the RANKL‐induced osteoclast formation in a dose‐dependent fashion without inducing cytotoxicity under the concentration of 12.5 μM. It exerted remarkable suppressive effects on the development of actin rings, the bone resorption, and the expressions of osteoclastogenesis‐related gene and protein markers. The down‐regulation of c‐Jun N‐terminal kinase (JNK), protein kinase B (Akt), and inhibitor of nuclear factor kappa‐B (IκB) phosphorylation in the early signaling event and subsequent inhibition of the expression of c‐Fos and nuclear factor of activated T cells (NFATc1) might be involved in these effects. All these results indicated that PIDP might be a promising drug to treat bone‐related disorders. Abstract : Imidazole‐containing bisphosphonate of PIDP could significantly inhibit the RANKL‐induced osteoclast formation and exert remarkable suppressive effects on the development of actin rings, the bone resorption, and the expressions of osteoclastogenesis‐related gene and protein markers, which showed great potential as a drug to treat bone‐related disorders.